Apixaban and rivaroxaban in obese patients treated for venous thromboembolism: Drug levels and clinical outcomes. Issue 208 (December 2021) - Ballerie, Alice; Nguyen Van, Rémi; Lacut, Karine; Galinat, Hubert; Rousseau, Chloé; Pontis, Adeline; Nédelec-Gac, Fabienne; Lescoat, Alain; Belhomme, Nicolas; Guéret, Pierre; Mahé, Guillaume; Couturaud, Francis; et al.
Abstract: Background: Direct oral anticoagulants (DOAC) use remains challenging in obese patients treated for Venous-Thrombo-Embolism (VTE) due to the paucity of prospective and dedicated studies. Objective: To assess rivaroxaban and apixaban concentrations at different time-points after intake, in obese patients followed at a thrombosis center and treated for VTE; to define factors associated with DOAC levels outside the on-therapy ranges; and to evaluate bleeding and thrombosis rates during follow-up. Methods: Observational prospective study in two French University hospitals. Apixaban or rivaroxaban concentrations were measured after the first visit, regardless of last intake in obese patients receiving DOAC for VTE. Concentrations were compared to published reference values for non-obese patients. Demographic, clinical, biological and therapeutic data were collected. Univariate and multivariate analyses were performed to identify factors associated to DOAC concentrations outside the on-therapy ranges. Results: Out of the 146 patients included, 22 (15%) had DOAC concentrations outside the on-therapy ranges, mainly in the rivaroxaban group (n = 17). Age ≤ 63 years, use of rivaroxaban and time since last intake ≤8 h were associated with DOAC concentrations outside the on-therapy ranges, in multivariable analysis. During the median follow-up of 16 months, two (1%) patients receiving apixaban had recurrent VTE. No patient had major bleeding, 11 (8%) patients had minor bleeding. Conclusion: In this specific prospective bi-centric study dedicated to VTE obese patients, use of DOACs at fixed doses led to concentrations similar to those of non-obese patients in a high proportion of patients, without any effect of the BMI, and with risk-benefit profile comparable to non-obese patients. Highlights: Prospective bi-centric study dedicated to DOAC levels in obese patients being treated for VTE and followed in a thrombosis clinic 22/146 patients (15%) had DOAC concentrations outside the on-therapy ranges BMI and renal function were not associated with DOAC concentrations outside the on-therapy range 2 (1%) patients had recurrent VTE, none had major bleeding and 11 (8%) had minor bleeding